Description of Wistar Rat (Rattus norvegicus) Skin Mast Cells with Hematoxylin Eosin and Alcian Blue Safranin Staining: Gambaran Sel Mast Kulit Tikus Wistar (Rattus norvegicus) dengan Pewarnaan Hematoxylin Eosin dan Alcian Blue Safranin - Putri Kurniasiwi; Tangguh Ardi Tyasa (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
One of the steps in making histological preparations is staining. Staining is a stage that aims to simplify the process of observing tissue structure and also makes it easier to distinguish the parts of the tissue that will be observed. Before staining, mast cells are difficult to identify visually under a microscope. Hematoxylin eosin is a routine stain in histotechnics and alcian blue safranin is a special dye that can stain mast cells. Mast cells can be found at the boundaries of body tissue and the external environment, one of which is the skin. Mast cells found in the skin are located in the dermis of the skin. The aim of this study was to determine the histology of skin connective tissue mast cells in Wistar rat (Rattus norvegicus) preparations stained with hematoxylin eosin and Alcian blue safranin. This research uses a experimental laboratory research type with a qualitative descriptive research design. The results obtained from observations of the histology of mast cells in the connective tissue of the skin of Wistar rats (Rattus norvegicus) with hematoxylin eosin staining from 16 preparations were found to be 62.5% good and 37.5% unfavorable. Staining with alcian blue safranin of 16 preparations was found to be 81.25% good and 18.75% unfavorable. The research results from preparations stained with alcian blue safranin showed better results compared to preparations stained with hematoxylin eosin.